2018
DOI: 10.3390/su10020521
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes Toward Eco-Toilet Systems in Rural Areas: A Case Study in the Philippines

Abstract: Death due to diseases from poor sanitation is a serious global issue and it has become one of the priorities of the United Nations' Sustainable Development Goals (i.e., SDG6). This SDG6 aims to provide adequate improved sanitation facilities to over 2.3 billion people around the world who have no or limited access to sanitation, wherein more than two-thirds of these un-served people live in rural areas. One of the strategies for addressing this global issue is through emerging sustainable sanitation technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 25 publications
3
35
0
1
Order By: Relevance
“…Consequently, users might have negative perceptions of ease of use, which could negatively affect their perceptions of the technology's usefulness and their attitude towards the technology, thereby affecting their behavioral intention for usage. Such findings are supported by various studies [18,19,38].…”
Section: Discussion and Research Implicationssupporting
confidence: 85%
See 4 more Smart Citations
“…Consequently, users might have negative perceptions of ease of use, which could negatively affect their perceptions of the technology's usefulness and their attitude towards the technology, thereby affecting their behavioral intention for usage. Such findings are supported by various studies [18,19,38].…”
Section: Discussion and Research Implicationssupporting
confidence: 85%
“…The results also demonstrated that the perceived usefulness of ETS can also be enhanced by improving the ease of use of environmental technology, as well as by creating demand for sanitation in the pilot community. By comparing the results, the outcomes generated by the PLS-SEM model in this study and the multiple linear regression in the previous study [19] were similar. Therefore, this study confirmed that PLS-SEM could be an alternative approach for predicting behavioral intention in C-TAM-TPB models.…”
Section: Discussion and Research Implicationssupporting
confidence: 63%
See 3 more Smart Citations